Strategic Motives Drive Proposers to Offer Fairly in Ultimatum Games: An fMRI Study - Yin-Hua Chen (Nature Portfolio, 2017)
Abstract The hypothesis of strategic motives postulates that offering fairly in the Ultimatum Game (UG) is to avoid rejection and receive money. In this fMRI study, we used a modified UG to elucidate how proposers reached decisions of offering fairly and to what extent they considered offering selfishly with different stakes. We had proposers choose between a fair and a selfish offer with different degrees of selfishness and stake sizes. Proposers were less likely and spent more time choosing the fair offer over a slightly-selfish offer than a very selfish offer independent of stakes. Such choices evoked greater activation in the dorsal anterior cingulate cortices that typically involve in allocation of cognitive control for cost/benefit decision making. Choosing a fair offer in higher stakes evoked greater activation in the anterior cingulate gyrus (ACCg) and the areas that previously have been implicated in reward and theory of mind. Furthermore, choosing a slightly selfish offer over a fair offer evoked greater activation in the anterior cingulate sulcus, ACCg, ventral tegmental area (or substantia nigra) and anterior insular cortex signalling the higher gain and implying higher rejection risk. In conclusion, our findings favoured the hypothesis that proposers offer fairly based on the strategic motives.